A study on the relationship between co-curricular and grades among fourth year students of San Jose National High School S.Y. 1998-1999 - De La Sierra, Elvira A. (1999)
The study was conducted to determine the relationship between Co- Curricular Activity and Grades among Fourth Year students of San Jose National High School. This was also done to determine the underlying reasons and effects to students who are involved or not involved to at least one or more than one Co- Curricular Activity based on their Second Grading Period. There are 63 respondents who were taken randomly from six sections by using 19% of the total population to determine the sample size. The researcher deliberately made the questionnaire. There are two variables investigated in this study: Co- Curricular Activity and Grades of the respondents.